Scaffold-based Drug Delivery for Cartilage Tissue Regeneration - Shalumon, K.T.; Chen, Jyh-Ping (Current Pharmaceutical Design, 2015)
Regenerative engineering is an advanced field comprising the collective benefit of biodegradable polymers with cells and tissue inducing factors. Current method of replacing the defective organ is through transplantation, but is limited due to immune rejection and availability. As a solution, new polymeric biomaterial-based threedimensional (3D) scaffolds in combination with cells and inducing factors were aroused to fulfil the existing demands. These scaffolds apply material science, biomedical technology and translational medicine to develop functional tissue engineering constructs. Presence of small molecules and growth factors guides the cell phenotypes to specific organ development. The 3D scaffold thus could also be favorably used as carriers for various types of drugs and genes, with the release profile fine-tuned by modulation of the scaffold’s morphology, porosity, and composition. An increasing trend was observed in recent years toward the combination of scaffolds and growth factors to fabricate a bioactive system, which not only provide a biomimetic biodegradable physical support for tissue growth but also explores biological signals to modulate tissue regeneration. In this review, along with general aspects of tissue engineering, we also discuss the importance of various scaffold architectures like nanofibers, hydrogels, beads, meshes, microspheres etc. in combination with specific drugs, growth factors and small molecules for cartilage regeneration. Growth factors may be incorporated into scaffolds by direct blending, physical adsorption, drop casting, surface grafting, covalent bonding, chemical immobilization, coaxial electrospinning, microparticle incorporation etc. This offers new possibilities for the development of biomimetic scaffolds that are endowed with a hierarchical architecture and sophisticated release kinetics of the growth factors. This review portrait the fundamentals of tissue engineering with emphasis on the role of inducing factors in scaffold based cartilage tissue regeneration.
Keywords: growth factors